(untitled) (Al-Academy, 2024)
The electronic advertisement is an advanced means of communication, keeping pacewith the times and the ease of access to the recipient in a way that suits the communication technical developments and human orientations. On influencing the recipient through the content of the suggestive metaphor, which dependsOn the juxtaposition of two contents, each of which carries a hypothetical significance of the content of the advertisement, as the metaphor is represented by the interdependenceof two meanings, the first for the real image, and the second for the relational construction according to the designer’s vision to form a virtual design structure within the formal metaphor that the designer invents in advertising works within an artistic formula that is sufficient and influential in the recipient , In this sense, the research problem raised by the researchers is summarized in the following two questions:- How is the virtual structure of the formal metaphor formed in electronic advertising?- What are the outcomes of the virtual construction of the formal metaphor in electronic advertising and its communication effectiveness?The importance of the research lies in the fact that it establishes intellectual and practical starting points for the axes of virtual construction and formal metaphor , in addition to that it is a scientific approach in employing the virtual formal metaphor in electronic advertising.The current research aims to reveal the mechanisms of employing the virtual construction of the formal metaphor in electronic advertising.